The SVEC III vectorcardiographic lead system. - Malmivuo, J.A (IEEE Engineering in medicine and biology magazine)
The properties of the stereovectorelectrocardiography (SVEC) III vectorcardiographic (VCG) lead system designed by Schmitt and Simonson are described. The theoretical and clinical aspects of this system are compared with the two other widely applied systems, of Frank and McFee. The theory and short history of VCG recording are also discussed.